Nigeria’s Experience Publishing Budget Allocations : A Practical Tool to Promote Demand for Better Governance - Songwe, Vera; Francis, Paul; Rossiasco, Paula; O'Neill, Fionnuala; Chase, Rob (World Bank, Washington, DC, 2012)
Since January 2004, the Nigerian Federal Ministry of Finance has taken an initiative to improve transparency at all levels of government, particularly the sub-national level. Every month, it publishes the federal, state, and local government shares of revenue from the country's federal account. From its inception, then Finance Minister Ngozi Okonjo-Iweala led this initiative as one of many efforts to improve public expenditure management, itself part of a broader set of institutional and governance reforms. Nigeria's effort to publish budgets is a leading example of how transparent information is essential to allow citizens to participate effectively in governance, hold authorities to account, and thereby enhance development effectiveness. The intuition behind this burgeoning awareness is clear. Like for other good things, the best governance outcomes result when there is a free flow of information between those supplying government services and those demanding those services.